2022
DOI: 10.1177/09721509221135927
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Financial Inclusion on Reducing Poverty and Income Inequality in South Asia: Evidence from a CS-ARDL Approach

Abstract: This study aims to examine the effects of financial inclusion on poverty reduction and income inequality with a focus on South Asian economies from 2004 to 2020 by employing dynamic panel models augmented with a comprehensive composite financial inclusion index and a set of well-known macroeconomic predictors. The primary results confirm the long-run relationships between financial inclusion, poverty headcount ratio and the Gini index, while the results of the cross-sectionally augmented autoregressive distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…The authors employed system GMM and panel corrected standard estimation technique and report that FD, ICT access, availability and usage played remarkable role in removing severity and intensity of poverty in SSA countries. A more recent study by Azimi (2022) examined the impact of financial inclusion on poverty alleviation in case of eight south Asian economies from 2004 to 2020. Using cross-sectionally augmented autoregressive distributed lag model (CS-ARDL), the authors found that financial inclusion is effective in reducing poverty and income inequality in south Asia both for short-run and long-run.…”
Section: Poverty In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…The authors employed system GMM and panel corrected standard estimation technique and report that FD, ICT access, availability and usage played remarkable role in removing severity and intensity of poverty in SSA countries. A more recent study by Azimi (2022) examined the impact of financial inclusion on poverty alleviation in case of eight south Asian economies from 2004 to 2020. Using cross-sectionally augmented autoregressive distributed lag model (CS-ARDL), the authors found that financial inclusion is effective in reducing poverty and income inequality in south Asia both for short-run and long-run.…”
Section: Poverty In Indiamentioning
confidence: 99%
“…The optimists on the other hand believe that FD is a viable developmental tool helpful in combating poverty (Odhiambo, 2009; Rewilak, 2017; Bolarinwa et al ., 2021; Azimi, 2022). These scholars argue that FD helps poor to get access to financial services like credit facilities, insurance, savings, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the Asian context, financial inclusion indicators such as bank branches, deposit accounts, and the number of loans granted significantly impact income inequality in the long run [19]. Moreover, in South Asian countries, comprehensive financial inclusion efforts have proven effective in reducing poverty and income inequality, emphasizing the importance of factors such as institutional quality and credit to the private sector [20]. Therefore, expanding financial inclusion is crucial in Indonesia to break the cycle of poverty and increase economic opportunities for marginalized groups.…”
Section: Introductionmentioning
confidence: 99%